2016
DOI: 10.1186/s40064-016-2020-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid compared with corticosteroid injections for the treatment of osteoarthritis of the knee: a randomized control trail

Abstract: BackgroundOsteoarthritis (OA) is the most common chronic condition of the joints that takes place when the cartilage or a low friction surface between joints breaks down which leads to pain, stiffness and swelling. The purpose of the present study was to evaluate the therapeutic effect of intra-articular hyaluronic acid (HA) in comparison to corticosteroids (CS) for knee osteoarthritis.Methods140 patients with knee osteoarthritis, who were followed for 3 months, were randomized to receive intra-articular injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 34 publications
10
41
0
Order By: Relevance
“…Askari et al compared intra articular hyaluronic acid with steroid in 140 cases. 20 They evaluated Western Ontario and McMaster University Osteoarthritis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and the visual analog pain scores and found superior results with intraarticular hyaluronic acid as compared to intraarticular steroid for osteoarthritis of knee, which is similar to our study.…”
Section: Discussionsupporting
confidence: 85%
“…Askari et al compared intra articular hyaluronic acid with steroid in 140 cases. 20 They evaluated Western Ontario and McMaster University Osteoarthritis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and the visual analog pain scores and found superior results with intraarticular hyaluronic acid as compared to intraarticular steroid for osteoarthritis of knee, which is similar to our study.…”
Section: Discussionsupporting
confidence: 85%
“…Intraarticular injected HA therapy shown to have prolonged effects in relieving pain compared to other similar treatments. This is consistent with other published studies to date [14,29,30].…”
Section: Discussionsupporting
confidence: 93%
“…They found better results with intraarticular Hyaluronic acid as compared to intra-articular steroid for osteoarthritis of knee. 13 In our study, with combination therapy we also found better results.…”
Section: Discussionsupporting
confidence: 72%